Implementasi Buku Cerita bergambar Rico dan Kata Ajaib di Sekolah untuk Menanamkan Nilai Sopan Santun di SD Negeri 16 Kota Langsa - Lidia Agnesia Lumban Batu; Lhutfia Wahyu Safutri (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Instilling politeness values ​​in elementary school students is very important to shape their character from an early age. In SD Negeri 16 Langsa City, the picture story book Rico and the Magic Words are used as a learning medium to instill politeness values. This study shows that picture story books can help improve students' character, especially in terms of politeness. This is due to the combination of attractive images, a simple but meaningful storyline, and a moral message that is easy for children to understand. Polite expressions such as "please", "sorry", "thank you", and "excuse me" are used in the story that are fun and related to students' daily lives. They are included contextually in this story. Therefore, this media is very appropriate to be used during learning in educational institutions.